Social perception of the process of rural shrinkage: Application of loss mapping method in one of Hungary's inner peripheral regions - Kovács, Tibor; Ruszkai, Csaba; Csáfor, Hajnalka; Vasvári, Mária (Bulletin of Geography. Socio-economic Series, 2024)
In our study, we examined six demographically declining and shrinking settlements in a traditional Hungarian cultural region, Greater Cumania, which is considered an internal peripheral region: we used statistical data and development documents, loss mapping and the Kruskal–Wallis test methodology. Analysis based on loss mapping of the six municipalities showed that, on average, municipalities rated their losses as slightly less severe than moderate. The statistical test showed that, although their natural and demographic conditions are very similar, the municipalities have followed a markedly different development path, with differences in potential for emerging from their peripheral existence and in resilience to challenges. In the light of these analyses, it can be concluded that the source of the problem is basically expressed in terms of qualities of the local society: the average is below the national average education level, and its level of cultural aspiration is very low. The decline of local societies is clear: the study does not predict development based on endogenous internal resources, but rather a slow decline, which is still slow today, but which is likely to accelerate in the light of global, national and local socio-economic, political and environmental processes.